Development and validation of selected biomarkers for the health status of the Nile crocodile (Crocodylus niloticus) and sharptooth catfish (Clarias gariepinus) - Botha, Catherine Frances (University of Pretoria, 2015)
Thesis (PhD)--University of Pretoria, 2014.